3 - Parent-Child Communication on Sexuality-Related Matters in the City of Lagos, Nigeria - Kunnuji, Michael O. N. (Africa Development, 2021)
Several studies have documented how the sexual activities of young people and the social context in which these activities take place heighten youth susceptibility to sexually transmitted infections, including HIV. There are contrasting findings on the role of parent-child communication (PCC) in shaping young people’s sexual behaviour. This paper provides answers to questions on gender differentials in parents’ involvement in PCC; age and gender differentials in young people’s involvement in PCC; and the relationship between exposure to PCC and sexual activities. Using data from a survey of 1,120 young people in the city of Lagos, the study shows that mothers are more involved in discussing sexuality related matters with their children than fathers, and where fathers are involved alone or in conjunction with mothers, the child is likely to be male. The study further shows that while PCC may not prevent or reduce sexual activities among young people, it does not increase it either, but is significantly related to safe sex practice in the population.